Key Agreement Scheme Based on Smart Cards - Ekal, Graygorry Brayone; Shahril Ismail, Eddie; Farhan bin Sabdin, Abdul Rahman (Enthusiastic : International Journal of Applied Statistics and Data Science, 2023)
An efficient roaming service over wireless networks is essential for mobile users. It allows mobile users to seamlessly access the services provided by the home agent without losing connectivity when they visit a foreign network. This handover communication happens with the help of a foreign agent. In most cases, the communication between the mobile user and the foreign agent occurs over an unsecured channel. Therefore, researchers have proposed various authentication schemes to protect data transmitted over this unsecured channel. Most of the proposed schemes are focused on key agreement schemes. However, the key agreement schemes researchers have submitted are primarily high in computational and communication costs. Therefore, this research proposed an authenticated key agreement scheme based on passwords and smart cards with lower computational and communication costs without compromising the scheme’s security. This criterion was achieved due to using lower-cost operations and functions in the scheme. Moreover, the scheme’s development is based on the result of analyzing and improving other schemes proposed by other researchers.